Performance of Mg-Sn surface alloys for the sacrificial cathodic protection of Mg alloy AZ31B-H24. (1st April 2019) - Glover, C.F.; Cain, T.W.; Scully, J.R.
Highlights: Mg-1Sn galvanically protects AZ31B-H24 for 24 h with 95% efficiency. Mg-5Sn shows only partial galvanic protection of AZ31B-H24. Mg-1Sn alloy shown to have a higher self-corrosion rate Mg-5Sn alloys. Abstract: Three solid solution Mg-xSn (x = 1, 5, 10 wt%) alloys are evaluated as candidates for the sacrificial cathodic protection of AZ31B-H24. The performance of each alloy was studied in situ with global and local measurements of galvanic couples between Mg-Sn alloys and AZ31B-H24 when immersed in 0.6 M aqueous NaCl solution. Mg-1Sn was shown to galvanically protect AZ31B-H24 for 24 h with 95% efficiency. Polarity reversal was observed for Mg-5Sn during the initial 10 h, after which protection was offered; and Mg-10Sn provided no protection. Self-corrosion rates of 60% and 52% were observed for Mg-1Sn and Mg-5Sn alloys, respectively.